2015
DOI: 10.2337/db14-1706
|View full text |Cite
|
Sign up to set email alerts
|

Gut Peptides Are Novel Regulators of Intestinal Lipoprotein Secretion: Experimental and Pharmacological Manipulation of Lipoprotein Metabolism

Abstract: Individuals with metabolic syndrome and frank type 2 diabetes are at increased risk of atherosclerotic cardiovascular disease, partially due to the presence of lipid and lipoprotein abnormalities. In these conditions, the liver and intestine overproduce lipoprotein particles, exacerbating the hyperlipidemia of fasting and postprandial states. Incretin-based, antidiabetes therapies (i.e., glucagon-like peptide [GLP]-1 receptor agonists and dipeptidyl peptidase-4 inhibitors) have proven efficacy for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 83 publications
3
35
0
Order By: Relevance
“…Pediatric reference intervals for markers of metabolic disease, steroid hormones, and vitamins a and E (HPLC, UPLC, LC-MS/MS). [53,54]). Similar to using the oral glucose tolerance test to determine impaired glucose tolerance and increased risk of type 2 diabetes, the "oral fat tolerance test" may be a helpful tool to determine impaired lipid tolerance and increased risk for cardiovascular events.…”
Section: Fasting Versus Postprandial Blood Samplingmentioning
confidence: 99%
“…Pediatric reference intervals for markers of metabolic disease, steroid hormones, and vitamins a and E (HPLC, UPLC, LC-MS/MS). [53,54]). Similar to using the oral glucose tolerance test to determine impaired glucose tolerance and increased risk of type 2 diabetes, the "oral fat tolerance test" may be a helpful tool to determine impaired lipid tolerance and increased risk for cardiovascular events.…”
Section: Fasting Versus Postprandial Blood Samplingmentioning
confidence: 99%
“…In this study, TRL-apoB48 stable isotopic enrichments were similar between treatments, suggesting that release of preformed chylomicron by intravenous glucose, if any, was not greater than by saline during the kinetic study. Gut hormones GLP-1 and GLP-2 are known to affect intestinal lipoprotein secretion 22 and GLP-2 rapidly promotes the release of preformed chylomicron. 21 Because GLP-2 cosecretes with GLP-1 on a 1:1 molar ratio 23 and GLP-1 secretion is stimulated by luminal but not vascular glucose, 24 it is unlikely that GLP-1 or GLP-2 played a significant role in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, the incretin-based antidiabetic drugs exenatide (a glucagon-like peptide-1 receptor agonist) and sitagliptin (a dipeptidyl peptidase-4 inhibitor) suppress intestinal lipoprotein production in the short term in humans (119,120). Incretin-based antidiabetic drugs also attenuated postprandial TG excursion in clinical trials (reviewed in Xiao et al [121]). Several recent CVD outcomes trials (122)(123)(124) have demonstrated the noninferiority of several such agents in T2D patients with established CVD or with increased CVD risks, and more trials with other agents are underway.…”
Section: Gut Hormones In the Regulation Of Postprandial Lipemiamentioning
confidence: 99%